Survei Tingkat Sportivitas Atlet Sepakbola Pada Pertandingan Antar Tim (Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the level of sportsmanship of soccer athletes in competitions between teams in Brebes Regency. This research is a mixed method research, namely a research method by combining two research methods at once. The target of this research is all athletes who participate in soccer competitions in Brebes Regency. The technique of collecting data is by observation, questionnaires, interviews, and documentation. The results of the study, the average value of the level of sports athletes in Brebes is 68 with a percentage of 77.71% which is included in the moderate category. With 7 teams of high scores, 2 teams of medium scores and 2 high scores. With the athlete's commitment value in competing reaching 77.17% in the moderate category, the athlete's social convention value in competing reaching 84.13% in the high category, the athlete's word score in competing reaching 62.5% in the low category, and the athlete's positive attitude value in competing. competed to reach 76.9% in the medium category. The conclusions obtained are the sports athletes' value in the team matches in Brebes Regency in 2019 in the medium category.